2013
DOI: 10.1111/ijs.12033
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity Magnetic Resonance Imaging in Stroke: An Evidence-Based Clinical Review

Abstract: Stroke is a common condition that may lead to various degrees of neurological deficit and long-term disability. It has become increasingly recognized that cortical reorganization of neuronal networks plays a significant role in regaining function following a focal brain injury. However, the mechanisms involved in this process are still not fully understood. Resting-state functional connectivity magnetic resonance imaging is a rapidly evolving scanning technique that has the potential to shed light into this ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
(89 reference statements)
0
9
0
Order By: Relevance
“…vision, attention, motor) and their topography recapitulates that of networks activated during tasks [510]. Notably, a growing number of studies indicates that stroke induces changes of functional connectivity within and between RSNs [1113] and that these changes correlate with behavioral impairment at acute [11,14,15] and chronic [11,16 ▪ ] phases (see Varsou et al [17], for a review). Here, we review the latest reports showing behaviorally relevant stroke-induced changes of functional connectivity at acute and chronic phases after stroke and after rehabilitation.…”
Section: Introductionmentioning
confidence: 98%
“…vision, attention, motor) and their topography recapitulates that of networks activated during tasks [510]. Notably, a growing number of studies indicates that stroke induces changes of functional connectivity within and between RSNs [1113] and that these changes correlate with behavioral impairment at acute [11,14,15] and chronic [11,16 ▪ ] phases (see Varsou et al [17], for a review). Here, we review the latest reports showing behaviorally relevant stroke-induced changes of functional connectivity at acute and chronic phases after stroke and after rehabilitation.…”
Section: Introductionmentioning
confidence: 98%
“…These studies mainly aimed to investigate the effect of stroke on cerebral networks and their value in predicting recovery (Grefkes and Fink, 2014). Most studies considered motor recovery and demonstrated a significant association between impaired performance and disrupted inter hemispheric functional connectivity (Carter, et al, 2010;Compston, 2011;Park et al, 2011;Golestani et al, 2013;Varsou et al, 2013;Dijkhuizen et al, 2014;Tsai et al, 2014;Xu et al, 2014). Recently, a study by Dacosta-Aguayo et al (2014) assessed the prognostic value of changes in rs-fMRI patterns in cognitive recovery after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Resting state functional connectivity (Biswal et al, ) in human stroke participants was first introduced in 2007 (Varsou et al, ). In rest paradigm, acquired during resting state functional MRI (rs‐fMRI), subjects do not have to perform a task, instead, they are asked to rest quietly with their eyes closed or open for several minutes (Greicius, ).…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is the third leading cause of death in industrialized countries and the most frequent cause of permanent disability in adults worldwide (Varsou et al, 2014;Lo et al, 2003;Donnan et al, 2008). Stroke is primarily either hemorrhagic or ischemic, and almost 80% of the stroke is ischemic (Banerjee et al, 2011).…”
Section: Strokementioning
confidence: 99%